Analysis of the criticality of flaws found in trunnion of grinding ball mills used in mining plants. (March 2016) - Neves, M.D.M.; Andrade, A.H.P.; Silva, D.N.
Abstract: The grinding ball mills are equipments present in mining plants, being important in the ore comminution circuits. Depending on numerous factors, such as, for example, inappropriate design, manufacturing, overloads, poor maintenance and inadequate operating procedures, flaws are developed in the structural components of this equipment. The structural components of a mill, basically, shell, heads and trunnions, besides high costs, have lead times that might reach three years, according to market demand. Therefore, it becomes increasingly necessary that any flaws in those components to be properly evaluated. This paper analyzed the fracture mechanics of flaws, such as cracks observed in a ball mill trunnion and compared the theoretical values of growth rate of these defects with actual values obtained through periodic inspections performed in this component. The cracks nucleation was caused by lack of lubrication in the trunnion bearings, generating circumferential thermal stresses, thus the estimated temperature of the trunnion and bushing contact achieved 150 °C. The lack of lubrication was originated by a logic failure which allowed the mill to start and run over the trunnion bearing bushing without the lubrication system to be turned on, that is, without oil film. The logic failure was caused by an operator fault. During the analyzed period, the results obtained by the standard BS7910 proved to be closest to the actual values than the standard ASME, Section XI, Appendix A. Highlights: Oil lubrication failure on grinding mill trunnion bearings causes thermal stresses in surfaces and cracks at low stress region. A contact temperature of 150 °C may causes a stress over the yield strength of the trunnion nodular cast iron. The use of standard BS 7910 on fatigue crack propagation in the trunnion proved to be more accurate compared to ASME Section XI.